Development of Snakes and Ladders Media Based on Blora Local Wisdom in Practicing Writing Skills in Indonesian Language Subjects for Elementary School Students - Pratama, Galih Cahya; Yuniawan, Tommi; Purwati, Panca Dewi (Proceedings of International Conference on Science, Education, and Technology, 2025)
The problem at SDN Bacem 02 Blora is related to the low writing ability of students. In this case, the researcher wants to design a snake and ladder media in which a story based on Blora's local wisdom is inserted. The purpose of this study is to develop a snake and ladder media to train students' writing skills in the Indonesian Language subject in elementary schools. The research was conducted using the development method (Research and Development), using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques used questionnaires from media experts, questionnaires from material experts, and assessments on students' writing skills in the Indonesian Language subject in the form of graphs. The results in the development of the snake and ladder media were 91% from media experts and 96% from material experts. Then, from the writing ability, it can be seen in the graph that always increases in each meeting.